WADAH KOMUNITAS GOTONG ROYONG CBS - Bryan Marco Wijaya; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2020)
The project, which is located in Cipinang Besar Selatan (CBS) sub-district, has become a prototype of the CBS community's daily life.